Novel PGS/PCL electrospun fiber mats with patterned topographical features for cardiac patch applications - Tallawi, Marwa; Dippold, Dirk; Rai, Ranjana; D'Atri, D.; Roether, Judith; Schubert, Dirk W.; Rosellini, E.; Engel, Felix; Boccaccini, Aldo R. (Materials Science and Engineering C, 2016)
Nano- and micro-scale topographical features play a critical role in the induction and maintenance of various cellular properties and functions, including morphology, adhesion, gene regulation, and cell-to-cell communication. In addition, recent studies have indicated that the structure and function of heart tissue are also sensitive to mechanical cues at the nano- and micro-scale. Although fabrication methods exist for generating topographical features on polymeric scaffolds for cell culture, current techniques, especially those with nano-scale resolution, are typically complex, prohibitively expensive and not accessible to most biology laboratories. Here, we present a simple and tunable fabrication method for the production of patterned electrospun fibers that simulate the complex anisotropic and multi-scale architecture of cardiac tissue, to promote cardiac cell alignment. This method is based on the combination of electrospinning and soft lithography techniques, in which electrospun fibers, based on a blend of poly(glycerol sebacate) and poly(caprolactone), were collected on a patterned Teflon-coated silicon wafer with imprinted topographical features. Different surface topographies were investigated, such as squares and grooves, with constant or different interspatial distances. In vitro cell culture studies successfully demonstrated the alignment of both C2C12 myoblasts and neonatal rat cardiomyocytes on fabricated electrospun patterned surfaces. C2C12 cells were cultured over a period of 72h to study the effect of topographical cues on cell morphology. Cells attached within the first 8h after seeding and after 24h most of the cells started to align responding to the topographical cues. Similarly, cardiomyocytes responded to the topographical features by aligning themselves and by expressing Connexin 43 along cellular junctions. Summarizing, we have developed a new method with the potential to significantly promote cardiac tissue engineering by fabricating electrospun fibers with defined topographical features to guide and instruct donor and/or host cells.
EVALuna:34665